Delivering the Thinking Healthy Programme for perinatal depression through peers: an individually randomised controlled trial in India. (February 2019) - Fuhr, Daniela C; Weobong, Benedict; Lazarus, Anisha; Vanobberghen, Fiona; Weiss, Helen A; Singla, Daisy Radha; Tabana, Hanani; Afonso, Ejma; De Sa, Aveena; D'Souza, Ethel; Joshi, Akankasha; Korgaonkar, Priya; et al.
Summary: Background: The Thinking Healthy Programme (THP) is a psychological intervention recommended for the treatment of perinatal depression. However, efforts to integrate the intervention at scale into the routines of community health workers who delivered the THP when it was first evaluated were compromised by the competing responsibilities of community health workers. We aimed to assess the effectiveness and cost-effectiveness of THP peer-delivered (THPP) in Goa, India. Methods: In this single-blind, individually randomised controlled trial, we recruited pregnant women aged 18 years or older who scored at least 10 on the Patient Health Questionnaire-9 (PHQ-9) from antenatal clinics in Goa. Participants were randomly allocated (1:1) to receive enhanced usual care (EUC; so-called because, in India, perinatal depression is not typically treated) only (control group) or THPP in addition to EUC (intervention group) in randomly sized blocks that were stratified by area of residence (urban or rural). Group allocations were concealed from participants and researchers before assignments were made by use of sequentially numbered opaque envelopes. The primary outcomes were the severity of depressive symptoms (assessed by PHQ-9 score) and the prevalence of remission (defined as a PHQ-9 score of less than 5) in participants with available data 6 months after childbirth, which was assessed by researchers who were masked to treatment allocations. We analysed outcomes by intention to treat, adjusting for covariates that were defined a priori or that showed imbalance at baseline. The trial is registered withClinicalTrials.gov, numberNCT02104232 . Findings: Between Oct 24, 2014, and June 24, 2016, we assessed 118 260 women for their eligibility for screening, of whom 111 851 (94·6%) women were ineligible. 6409 (5·4%) women were eligible for screening and 6369 (99·4%) of these women consented to be screened with the PHQ-9 (40 women did not consent), of whom 333 (5·2%) screened positive for depression (defined as a PHQ-9 score of at least 10). We enrolled 280 (84·1%) women with perinatal depression; 140 women were assigned to the THPP and EUC group and 140 women to the EUC only group. The final treatment was given on May 27, 2017. The final 6-month outcome assessment was completed on June 9, 2017. At 6 months after birth, 122 (87%) women in the THPP and EUC group and 129 (92%) women in the EUC only group were assessed for the primary outcome. There was a higher prevalence of remission at 6 months after birth in the THPP and EUC group compared with the EUC only group (89 [73%] women in the intervention group vs 77 [60%] women in the control group; prevalence ratio 1·21, 95% CI 1·01 to 1·45; p=0·04), but there was no evidence of a difference in symptom severity between the groups (mean PHQ-9 score 3·47 [SD 4·49] in the intervention group vs 4·48 [5·11] in the control group; standardised mean difference −0·18, 95% CI −0·43 to 0·07; p=0·16). There was no evidence of significant differences in serious adverse events between the groups. Interpretation: THPP had a moderate effect on remission from perinatal depression over the 6-month postnatal period. THPP is relatively cheap to deliver and is cost-saving through reduced health-care, time and productivity costs. Funding: National Institute of Mental Health (USA).